PENERAPAN MODEL PEMBELAJARAN BERBASIS MASALAH(PBM) UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS IV SD NEGERI 013 BALAMJAYA KECAMATAN TAMBANG - Syaipul Anam Azhar Makmum Anam Azhar Makmum; Damanhuri Daud Damanhuri Daud; Eddy Noviana Eddy Noviana (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This research is motivatedby the low student learning outcomes inscience subjects with an average grade 51,10 and value 0f minimum completenesscriteria (KKM) 65. From 32 studenst about 10 students who reach KKM and 22students who did not reach the KKM. To overcome the problem, one model of learningthat can improve student learning outcomes in learning science is a model centeredlearning and prioritize real experience. The learning model is the model of probelmbased learning. The research in the form of classroom action research (PTK), this studyaims to improve student learning outcomes IPA fourth grade SDN 013 Balamjaya. Thisthesis shows that the probelm based learning model can improve learning outcomes. Itcan be seen from the average value increased student learning outcomes. On the basisof an average score of student learning outcomes are 51,10 and 52,19 in cycle onebeing an increase of 2.13%. while the average student learning outcomes in the secondcycle, namely 60.78 an increase of 16.45%. the third cycle average of 70.46 studentlearning outcomes increased by 15.92%. data analysis of student activity during use ofprobelm based learning model at the first meeting of the cycle 55%, in the second 60%,in the first two meetings cycle 70%, in yhe second meeting 80%. In the first cycle ofthree meetings by 90%, and at the second meeting by 95%. This means probelm basedlearning model can improve student learning outcomes fourth grade SDN 013Balamjaya.Key words: Probelm based learning, learning outcomes IPA.